2018
DOI: 10.1016/j.ajpath.2017.10.023
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-31-3p Is Involved in Substance P (SP)-Associated Inflammation in Human Colonic Epithelial Cells and Experimental Colitis

Abstract: Substance P (SP) mediates colitis. SP signaling regulates the expression of several miRNAs, including miR-31-3p, in human colonocytes. However, the role of miR-31-3p in colitis and the underlying mechanisms has not been elucidated. We performed real-time PCR analysis of miR-31-3p expression in human colonic epithelial cells overexpressing neurokinin-1 receptor (NCM460 NK-1R) in response to SP stimulation and in NCM460 cells after IL-6, IL8, tumor necrosis factor (TNF)-α, and interferon-γ exposure. Functions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Cetuximab is known to trigger intratumor inflammatory infiltration in liver metastases, with an enrichment of CD3 À , CD8 À , and CD56 þ cells (37). Given miR-31-3p is also involved in immune and inflammatory cells homeostasis (38)(39)(40)(41), its overexpression might sometimes be due to intratumor infiltration from lymphocites or inflammatory cells. Under these circumastances, despite tissue microdissection, contamination by inflammatory cells might potentially lead to a bias in miR-31-3p scoring when using high sensitivity RT-PCR-based assays.…”
Section: Resultsmentioning
confidence: 99%
“…Cetuximab is known to trigger intratumor inflammatory infiltration in liver metastases, with an enrichment of CD3 À , CD8 À , and CD56 þ cells (37). Given miR-31-3p is also involved in immune and inflammatory cells homeostasis (38)(39)(40)(41), its overexpression might sometimes be due to intratumor infiltration from lymphocites or inflammatory cells. Under these circumastances, despite tissue microdissection, contamination by inflammatory cells might potentially lead to a bias in miR-31-3p scoring when using high sensitivity RT-PCR-based assays.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it was hypothesized that high levels of miR-4521-3p may favor the inflammatory environment often observed in MSI tumors. The second candidate found to be upregulated in dT cells, miR-31-3p, has also been associated with intestinal inflammation (62). Olaru et al suggested that the expression of miR-31-3p increases during the progression of inflammation-associated intestinal neoplasia (63).…”
Section: Hct116-tgfbr2 (Fc) --------------------------------------mentioning
confidence: 99%
“…MCP-1, also called chemokine (C-C motif) ligand 2 (CCL2), is a pain-related inflammatory cytokine that recruits several types of immune cells to the sites of inflammation in the condition of tissue injury or infection [9]. MCP-1 production could be regulated by SP concentrations in different cell types [10][11][12], indicating that SP can stimulate MCP-1 production which attracts inflammatory cells to specific sites. The previous studies focused on the changes of the pain-related inflammatory cytokines such as interleukin (IL)-1, IL-6,12 IL-8, spinal macrophage inflammatory protein (MIP), MCP-1, vascular endothelial growth factor (VEGF), and regulated on activation, normal T expressed and secreted (RANTES) before and after cataract surgery of the first eye, however the neuropeptide SP has not been identified.…”
Section: Introductionmentioning
confidence: 99%